(untitled) (International Journal of Studies in Nursing, 2021)
Introduction: Exposure to the clinical learning environment is indispensable for the nursing students as it provides experiences which are basic and significant to the development of professional skills as well as bridge the theory-practice gap. Despite the importance of clinical learning, nursing students’ attitudes in the clinical environment has been a concern. Purpose: This paper reviewed the attitude of nursing students towards work in the clinical learning environment. Method: Electronic searches using scholarly databases were employed and only significant articles that met the review objective were utilized. Findings: This review revealed that there is a high rate of unauthorized student nurses’ absenteeism as majority are absent from clinical work without permission. There is also an appalling display of lateness behavior as students arrive at work after the scheduled time. Interestingly, most students are willing to carry out procedures while some are nonchalant due to the stressful and anxiety provoking tasks. Student nurses felt that there is an unspoken comparison, discrimination and disrespect displayed by their seniors and medical colleagues towards them. Conclusion: There is overwhelming evidence from literature supporting the negative attitudes of nursing students in the clinical environment. It was therefore recommended that students should be psychologically prepared in their schools before exposure to the clinical environment. There should be an effort to build students’ self-esteem and professional self-concept by the relevant authorities. Finally, to bridge the rift between inter-professionals, there is need for more social interaction opportunities where everyone will value what each member contributes to the team.